Deciphering Genomic Regions and Putative Candidate Genes for Grain Size and Shape Traits in Durum Wheat through GWAS - Uğur Sesiz (Agriculture, 2023)
Durum wheat is an economically and nutritionally important cereal. The increase in durum wheat yield is mostly associated with improving grain traits, and the grain size- and shape-related traits are directly related to wheat yield. In addition, grain size influences the seed germination rate and seedling vigor, which play key roles in stand establishment and yield. Thus, it is important to investigate grain traits both agro-morphologically and genetically. In this study, a panel of durum wheat, consisting of 146 genotypes, was evaluated for grain traits agro-morphologically and a genome-wide association study (GWAS) was conducted to dissect the genomic regions associated with these traits. As a result of the GWAS, a total of 41 marker-trait associations (MTAs) were identified on different chromosomes of durum wheat. Of these MTAs, only 11 were stable across environments. A BLAST search for the flanking sequences of every stable MTA in the Svevo genome identified 18 putative candidate genes directly associated with the seed traits of different plants, particularly wheat seeds. In conclusion, the annotation results and literature information provide strong evidence that the identified stable MTAs and their candidate genes may have important functions in the formation of wheat grain traits. After the validation of these MTAs with different fine-mapping and functional characterization studies, these loci may provide valuable information for geneticists and breeders to improve wheat yield.